2020
DOI: 10.1007/s11146-020-09787-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Market Maturity in Mutual Funds: Is Real Estate Different?

Abstract: Despite the lack of convincing evidence that active investment fund managers add value, the number of actively-managed US mutual funds has increased substantially over the last 25 years. While non-sector diversified mutual funds have received much attention, sector funds, except real estate mutual funds (REMFs), have not. In this paper, we provide new and more robust evidence on the performance of active REMFs compared to all actively managed mutual funds. We use the Carhart four-factor model with an additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Moreover, recent investigations by Lantushenko and Nelling (2020) observed a decline in activity among real estate fund managers, with geographically diversified real estate mutual funds failing to outperform. MacGregor et al (2021) did not find substantial evidence supporting the outperformance of global real estate mutual funds compared to other actively managed funds, even in the long term. Despite the exponential growth of real estate mutual funds highlighted by Malhotra's study (Malhotra 2020) due to low interest rates and increased real estate demand, the average turnover ratio for real estate mutual funds decreased significantly after 2009, indicating reduced portfolio management activity.…”
Section: Previous Studiesmentioning
confidence: 68%
“…Moreover, recent investigations by Lantushenko and Nelling (2020) observed a decline in activity among real estate fund managers, with geographically diversified real estate mutual funds failing to outperform. MacGregor et al (2021) did not find substantial evidence supporting the outperformance of global real estate mutual funds compared to other actively managed funds, even in the long term. Despite the exponential growth of real estate mutual funds highlighted by Malhotra's study (Malhotra 2020) due to low interest rates and increased real estate demand, the average turnover ratio for real estate mutual funds decreased significantly after 2009, indicating reduced portfolio management activity.…”
Section: Previous Studiesmentioning
confidence: 68%
“…This is explained by information asymmetry, which means that these managers know their sectors better than other types of fund managers (Kaushik et al, 2010). In contrast, studies which have considered sector funds (Dellva et al, 2001;Tiwari and Vijh, 2001;Eakins and Stansell, 2007;Kaushik et al, 2010;MacGregor et al, 2020) have found that some sectors, such as technology, health care and utilities, can outperform but only during specific periods. And Khorana and Nelling (1997) suggested that the overall risk levels of sector funds are indistinguishable from small-cap or aggressive-growth funds.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Earlier studies by Kallberg et al (2000) and Gallo et al (2000) found outperformance when real estate market returns were poor, which is attributed to real estate market inefficiency. However, more recent studies (O'Neal and Page, 2000;Lin and Yung, 2004;Rodriguez, 2007;Chiang et al, 2008;Chou and Hardin, 2014;MacGregor et al, 2020) have found little or no evidence to support significant outperformance attributable to real estate mutual fund (REMF) managers' superior skills, regardless of the benchmarks used for the market or the real estate sector. Ferreira et al (2013) considered active mutual funds in 27 countries and used country-specific Carhart benchmarks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The S-REIT market, characterized by its developed and mature nature, boasts a greater number of publicly traded REITs and a larger market capitalization compared to the M-REIT market. This difference in market maturity not only influences diversification strategies but also sets distinct investor expectations, impacting the performance and strategic planning (MacGregor et al ., 2021) of REITs in each market. In Malaysia, where the financial market is less sophisticated, diversification within the REIT sector has been shown to add significant value.…”
Section: Implications and Conclusionmentioning
confidence: 99%